The final wish [videorecording (DVD)] - Shaye, Lin, 1944-; Welch, Michael, 1987-; Bolona, Melissa (Cinedgim Entertainment Corp., 2019)
After the death of his father, Aaron returns home to help his grief-stricken mother and to confront his past. Going through his dad's belongings, he comes across a mysterious item that is more than it seems. As his wants and wishes come true, Aaron thinks his prayers have been answered until he realizes the price of this good fortune is more than he bargained for.